Utilization of the Ministry of Religious Affairs PINTAR Application as an Open Learning Material Source for PAI Teachers in the Merdeka Curriculum Training in Madrasah Ibtidaiyah - Nadhiroh, Yulsiva Anissatun; Rusydiyah, Evi Fatimatur (Yayasan Rahmat Islamiyah, 2025)
The Ministry of Religious Affairs to improve the quality of the State Civil Apparatus (ASN) and its partners such as teachers in madrasas is realized in one of them by holding the Massive Open Online Course (MOOC) PINTAR. The program, initiated by Pusdiklat Kemenag since 2022, has been attended by more than one million participants since July 2024. This application is an open learning resource or Open Educational Resources (OER) for teachers or employees under the auspices of the Ministry of Religion. This study examines how the utilization of this application on Islamic Religious Education teachers in Madrasah Ibtidaiyah as a means of professional development regarding the independent curriculum for Islamic Education teachers in madrasah. This research uses qualitative methods with the type of field research, data sources in this study using observation and interview techniques. The result of this study is that the PINTAR application can increase understanding of the concept of the Merdeka Curriculum for Madrasah Ibtidaiyah teachers, especially regarding the project for raising the profile of Pancasila and Rahamtan lil Alamin students (P5PPRA)